Rationally designed FeOx@CuOx/FTO dendritic hybrid: A sustainable electrocatalyst for efficient oxygen evolution reaction. (1st July 2022) - Manzoor, Sumaira; Sadaqat, Maira; Hussain Shah, Jafar; Gouadria, Soumaya; Hussain, Fayyaz; Saleem Joya, Khurram; Najam-ul-Haq, Muhammad; Aman, Salma; Trukhanov, A.V.; Naeem Ashiq, Muhammad
Graphical abstract: Highlights: The electrochemically oxidized electrode requires low overpotential to drive 1mAcm −2 (210 mV) and 10 mAcm −2 (257 mV) current density. 3% FeOx @CuOx derived via electrochemical oxidation, enhances the electrochemical active surface area consequently increases the exposure of active sites. The synthesized electrode obtained current density of 10mAcm −2 and 80mAcm −2 at low overpotential of 257 mV and 320 mV respectively, with small tafel slope (37 mVdec −1 ). Abstract: The development of highly efficient and reliable electrocatalyst for oxygen evolution reaction is highly demanded by the energy conversion and storage devices. In this work, synergism effect of iron and copper is investigated for the oxygen evolution reaction. Here we reported the facile synthesis of microspheres of CuOx decorated with dendritic nanoarrays of FeOx (3% FeOx @CuOx ) via spray coated on the FTO substrate used as an OER electrocatalyst. As oxides of copper (CuOx ) are resistive to undergo oxidation, therefore act as strong platform where, heterostructures 3% FeOx @CuOx expose numerous active sites as well as the synergistic effect of copper and iron can catalyze the OER reaction at low overpotential and increases the durability of electrocatalyst as well. Moreover the optimization of Fe ions concentration mediate the electrochemical active surface area and intrinsic activity of electrocatalyst. Interestingly, it is found that after electrochemical oxidation by continuous CV cycling in 1.0 M KOH solution promotes the OER performance. The synthesized electrode obtain current density of 10 mAcm −2 and 80 mAcm −2 at low overpotential of 257 mV and 320 mV respectively, with small tafel slope (37 mVdec −1 ) for 3% FeOx @CuOx as compared to 3% FeOx @Cu2 O. Moreover, the increase in electrochemical surface area and intrinsic activity of resultant material 3% FeOx @CuOx enhances considerably. Both experimental and computational studies indicate the auspicious surface properties for the adsorption and desorption of intermediates involved in the OER process. This can be attributed to the phase transformation of Cu2 O to CuO during electrochemical oxidation process, changing the electronic structure of active sites which led to the generation of Oxides/hydroxides of iron and enhancing the Fe-O bonding, overall benefiting the OER process. The activity of optimized 3% FeOx @CuOx is comparable to the state of electrocatalyst RuO2 .